2022
DOI: 10.3390/land11030439
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Change in the Willingness to Pay for a More Sustainable Tourist Destination in a World Heritage City

Abstract: The willingness to pay for sustainable tourism products and services has been widely discussed in the scientific literature. However, change in the willingness to pay over time has rarely been analysed. Such studies are important for understanding the impact that the increasing debate on sustainability, including environmental, economic, and social aspects, may have had on the willingness of tourists to pay more in order to ensure the sustainability of destinations. The aim of this article is to assess how the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Similarly, the result of this survey also shows that most local respondents are willing to pay of RM 4.89 per person, which exceeded the current fee they imposed which is RM 3.00 (see Figure 1). This finding indicates that there is evidence suggesting some tourists are willing to pay a higher price to visit locations that are viewed as sustainable, giving sustainability an added value for destinations [9] because the likelihood of the respondents accepting a price increase is higher if they were informed about the purpose of the payment. On the other hand, some respondents believe that the park should not increase the admission fee because it may not have a positive impact, while some thought that it is the government's role to enhance and maintain the park.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Similarly, the result of this survey also shows that most local respondents are willing to pay of RM 4.89 per person, which exceeded the current fee they imposed which is RM 3.00 (see Figure 1). This finding indicates that there is evidence suggesting some tourists are willing to pay a higher price to visit locations that are viewed as sustainable, giving sustainability an added value for destinations [9] because the likelihood of the respondents accepting a price increase is higher if they were informed about the purpose of the payment. On the other hand, some respondents believe that the park should not increase the admission fee because it may not have a positive impact, while some thought that it is the government's role to enhance and maintain the park.…”
Section: Discussionmentioning
confidence: 90%
“…This method is useful as it is used in practice to represent the preferences of individuals as well as society in a variety of domains like the environment, education, health care, and others [5] . Valuation studies were conducted in developing countries, covering various types of ecosystems such as wetlands, national parks, and forests [2,9,14]. To manage and protect biodiversity, it is necessary to collect data on the economic worth of biodiversity conservation.…”
mentioning
confidence: 99%
“…For example, historic sites provide a sense of place and identity, a level of social inclusiveness and community participation [73], and the special cultural and biological values of urban heritage trees as natural heritage are also valued by residents [74]. Jurado-Rivas and Sanchez-Rivero investigated changes in tourists' willingness to pay for destinations in World Heritage cities, found that tourists' willingness to pay for sustainable tourism services has not increased, and proposed responsive countermeasures [75]. However, these studies have often been conducted in the context of traditional approaches to cultural heritage conservation management and have not yet examined the non-use values of cultural heritage in the context of sustainable and circular economy models.…”
Section: Assessment Of the Value Of The Estate Through Wtpmentioning
confidence: 99%
“…Therefore, instead of commercialising a place through an attractive logo or more orthodox marketing strategies, in the context of tourism linked to the land, place branding is increasingly understood as a mechanism to promote the place's quality and encourage meaningful links between visitors and residents in the tourist destination through shared experiences [65][66][67].…”
Section: Regional Agri-food Products and Restaurants Linked To Their ...mentioning
confidence: 99%